2003
DOI: 10.1051/0004-6361:20031472
|View full text |Cite
|
Sign up to set email alerts
|

The heterogeneous class ofλBootis stars

Abstract: Abstract. We demonstrate that it is arduous to define the λ Boo stars as a class of objects exhibiting uniform abundance peculiarities which would be generated by a mechanism altering the structure of their atmospheric layers. We collected the stars classified as λ Boo up to now and discuss their properties, in particular the important percentage of confirmed binaries producing composite spectra (including our adaptive optics observations) and of misclassified objects. The unexplained RV variables (and thus su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
96
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(97 citation statements)
references
References 51 publications
0
96
1
Order By: Relevance
“…The selective-accretion theory of Venn & Lambert (1990) is currently the most widely supported model. In the recent literature, Faraggiana & Bonifacio (1999); Gerbaldi et al (2003) and Faraggiana et al (2004) mention that binarity can play an underestimated role. The composite spectrum might mimic the spectrum of a truly underabundant single star.…”
Section: Discussionmentioning
confidence: 99%
“…The selective-accretion theory of Venn & Lambert (1990) is currently the most widely supported model. In the recent literature, Faraggiana & Bonifacio (1999); Gerbaldi et al (2003) and Faraggiana et al (2004) mention that binarity can play an underestimated role. The composite spectrum might mimic the spectrum of a truly underabundant single star.…”
Section: Discussionmentioning
confidence: 99%
“…Large inconsistencies between the atmospheric parameters derived from the calibration of visual photometric colour indices and the UV flux distribution, discussed by Gerbaldi et al (2003) for the stars observed by TD1, are also signs that the star is not a classical λ Boo.…”
Section: Duplicity Detection From Spectroscopic and Photometric Datamentioning
confidence: 99%
“…Binary systems detected by imaging are discussed in detail by Gerbaldi et al (2003). The measure of separation and magnitude difference made it possible to recognize that 12 objects, corresponding to 9% of the total, classified as λ Boo, are in reality binaries that cannot be resolved at the spectrograph entrance.…”
Section: Binary Stars Producing Composite Spectramentioning
confidence: 99%
See 2 more Smart Citations